Differential expression of homologous recombination DNA repair genes in the early and advanced stages of myelodysplastic syndrome - Valka, Jan; Vesela, Jitka; Votavova, Hana; Dostalova-Merkerova, Michaela; Horakova, Zuzana; Campr, Vit; Brezinova, Jana; Zemanova, Zuzana; Jonasova, Anna; Cermak, Jaroslav; Belickova, Monika (European journal of haematology, 2017)
BACKGROUND: The high incidence of mutations and cytogenetic abnormalities in patients with myelodysplastic syndrome (MDS) suggests that defects in DNA repair mechanisms. We monitored DNA repair pathways in MDS and their alterations during disease progression. METHODS: Expression profiling of DNA repair genes was performed on CD34+ cells, and paired samples were used for monitoring of RAD51 and XRCC2 gene expression during disease progression. Immunohistochemical staining for RAD51 was done on histology samples. RESULTS: RAD51 and XRCC2 showed differential expression between low-risk and high-risk MDS (P<.0001), whereas RPA3 was generally decreased among the entire cohort (FC=-2.65, P<.0001). We demonstrated that RAD51 and XRCC2 expression gradually decreased during the progression of MDS. Down-regulation of XRCC2 and RAD51 expression was connected with abnormalities on chromosome 7 (P=.0858, P=.0457). Immunohistochemical staining revealed the presence of RAD51 only in the cytoplasm in low-risk MDS, while in both the cytoplasm and nucleus in high-risk MDS. The multivariate analysis identified RAD51 expression level (HR 0.49; P=.01) as significant prognostic factor for overall survival of patients with MDS. CONCLUSIONS: Our study demonstrates that the expression of DNA repair factors, primarily RAD51 and XRCC2, is deregulated in patients with MDS and presents a specific pattern with respect to prognostic categories.
Keywords: DNA vazebné proteiny; oprava DNA; dospělí; Female; biologické markery; Rad51 Recombinase; Biomarkers; Adult; mladý dospělý; ženské pohlaví; rekombinasa Rad51; lidé; Bone Marrow; DNA Repair; Aged, 80 and over; Recombinational DNA Repair; prognóza; rekombinační oprava DNA; Myelodysplastic Syndromes; regulace genové exprese; kostní dřeň; myelodysplastické syndromy; Male; chromozomální aberace; Aged; Young Adult; DNA-Binding Proteins; Prognosis; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Gene Expression Regulation; Middle Aged; Chromosome Aberrations; Humans